APRESIASI SASTRA ISLAMI DI INDONESIA - Mulyono, Mulyono (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2008)
The current situation of Islamic literature in Indonesia shows significant and important development in relation to testhelic, thematic, market, society, publising industry and literary writing. This trend shows that Islamic literature in Indonesia groun well and covers wide readers from various levels. Literary apprecation from society especially from academic members of PTAI (Islamic Higher Education Institution) is needed to make Islamic literature exits quantitatively and qualitatively. The development of Islamic literature is integral part ofÂ  Islamic civilization development.